2022
DOI: 10.1021/acsomega.2c06151
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Electronic Structural Properties of the S3 State of Nature’s Water Oxidizing Complex: A Combined Study in ELDOR-Detected Nuclear Magnetic Resonance Spectral Simulation and Broken-Symmetry Density Functional Theory

Abstract: ELDOR-detected nuclear magnetic resonance (EDNMR) spectral simulations combined with broken-symmetry density functional theory (BS-DFT) calculations are used to obtain and to assign the 55 Mn hyperfine coupling constants (hfcs) for modified forms of the water oxidizing complex in the penultimate S 3 state of the water oxidation cycle. The study shows that an open cubane form of the core Mn 4 CaO 6 cluster explains the magnetic properties of the dominant S = 3 species in all cases studied experimentally with no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Another recent EPR analysis has instead concluded that S 3 has an open cubane structure. 24 Other S = 6 structures than the one found by Pantazis et al could, for example, be obtained by simply reversing the signs of the spins on some Mn(IV) centers and keep the open cubane. That should only marginally affect the energies and, therefore, not be important for the oxyl–oxo mechanism.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Another recent EPR analysis has instead concluded that S 3 has an open cubane structure. 24 Other S = 6 structures than the one found by Pantazis et al could, for example, be obtained by simply reversing the signs of the spins on some Mn(IV) centers and keep the open cubane. That should only marginally affect the energies and, therefore, not be important for the oxyl–oxo mechanism.…”
Section: Discussionmentioning
confidence: 87%
“…With the accuracy typical for the methods used here of about 3 kcal/mol, the closed cubane structure must, therefore, be ruled out as a possible S 3 state. Another recent EPR analysis has instead concluded that S 3 has an open cubane structure . Other S = 6 structures than the one found by Pantazis et al could, for example, be obtained by simply reversing the signs of the spins on some Mn­(IV) centers and keep the open cubane.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations